The Differentiate Effects of Resistance Training With or Without External Load on Young Soccer Players’ Performance and Body Composition - Moisés Falces-Prieto (Frontiers Media S.A., 2021)
Purpose: The purpose of this study was to examine the effects of 15 weeks (2/week) of two different resistance training (RT) programs [the self-load group (SG) vs. the overload group (OG)] on selected measures of physical performance in young male soccer players.Methods: The countermovement jump (CMJ), aerobic endurance (VO2 max), and body composition [body mass (BM), height (H), body fat percentage (% BF), and lean mass (LM)] were measured before and after the 15-week RT interventions. Subjects were randomized to treatments: 1. SG [age = 15.34 ± 1.34 years]; 2. OG [age = 16.28 ± 1.21 years].Results: The level of significance set for the study (p ≤ 0.05). Within-group analysis did report significant differences in all variables for the SG (p = 0.008 to 0.001; ES = −0.33 to 1.41, small to large) as in the OG (p = 0.001; ES = 0.82 to 1.30, large). Between-groups analysis reported differences in CMJ (F = 4.32; p = 0.004) for the OG.Conclusion: The main findings of this study indicated that RT with and without external load was effective in improving the measures of physical performance in young soccer players, with special attention to jumping ability, where the OG group was more effective. Furthermore, there is no interference to aerobic endurance. It is recommended that soccer coaches implement RT without external load in the early stages of training or in players with late maturation development and in those soccer clubs with limited material resources.